EFFECT OF CONTINUOUS ENHANCED VAGAL TONE ON DUAL ATRIOVENTRICULAR NODE AND ACCESSORY PATHWAYS - Hameed Ullah,; Muhammad Idrees Khan,; Asif Mehmood,; Yasir Hayat ,; Talia Mansoor,; Romana, (Journal of Ayub Medical College Abbottabad, 2026)
Background: Continuous increased vagotonus effect on dual atrioventricular (AV) node and accessory pathway requires a flexible concept in the field of cardiac electrophysiology. The AV node has a critical function in regulation of the heart´s electrical conduction and accessory pathways are abnormal alternate routes to which an impulse can be transmitted across, circumventing these checkpoints–causing arrhythmias such as atrioventricular re-entrant tachycardia (AVRT) or Wolff-Parkinson-White Syndrome (WPW). Objective was to evaluate the effect of continuous enhanced vagal tone on dual AV node physiology and accessory pathways, focusing on conduction properties, arrhythmia induction, and the success of catheter ablation. Methods: A prospective observational study was conducted in the Department of Cardiology, Hayatabad Medical Complex, Peshawar, between April 2023 and April 2024. The study included 250 patients with dual AV node physiology or accessory pathways, undergoing electrophysiological studies and catheter ablation. Continuous vagal stimulation was applied during these procedures to assess its impact on conduction delays, refractory periods, and arrhythmia induction. Statistical analysis was performed using Chi-square and logistic regression, with a significance level of p<0.05. Results: The mean PR interval delay during vagal stimulation was 202 ms, and the mean refractory period was 250 ms. Arrhythmias were induced in 35% of the patients. Catheter ablation was successful in 85% of cases, though 30% experienced recurrence of arrhythmia within one year. The results showed a significant association between continuous vagal tone and arrhythmia induction, as well as a protective effect of longer refractory periods against recurrence. Conclusion: Continuous enhanced vagal tone significantly influences the conduction properties of dual AV nodes and accessory pathways, increasing the likelihood of arrhythmias. While catheter ablation remains effective, these findings suggest that vagal modulation could be explored as a potential adjunct to improve long-term outcomes in patients with complex arrhythmias.